(untitled) (Experimental biology, 2015)
The species composition microalgae of lake Kopa represent Chlorophyta, Bacillariophyta, Cyanophyta and Euglenophyta. From these groups dominate Chlorophyta. As a result of research it was defined algological pure culture of green water-plants taken from the lake Kopa. In job the biotesting lakes on cultures of microseaweed allocated with water ecosystem of lake Kopa is carried out is especial on strain Chlorella sp-3K, distinguished fast duplicate and clearing ability of pollution of natural waters. As a result of biotesting, is revealed, that waters of lake Зеренда an average level toxicity: growth of crates average 15±0,52 mln/ml.